Pseudotibiozus Demange, 1970—millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae) - Enghoff, Henrik; Larsson, Tobias Berglund (Zootaxa, 2018)
The genus Pseudotibiozus Demange, 1970, is discussed, its type species, P. cerasopus (Attems, 1914) is re-described based on type and new material, and P. zophoribates sp. nov. is described from the West Usambara Mountains, Tanzania. The millipede faunas of the West and East Usambara Mts are compared.